2000
DOI: 10.1007/s002149900108
|View full text |Cite
|
Sign up to set email alerts
|

Relativistic electron densities in the four-component Dirac representation and in the two-component picture

Abstract: Analytic formulae of the relativistic radial functions of hydrogen-like atoms in the four-component standard Dirac picture and in two approximations, (Pauli and ZORA), to the two-component (so-called SchroÈ dinger or Newton±Wigner) picture and graphs of the respective relativistic changes of densities are presented and discussed. The two dierent pictures of the Dirac density of charge position and of the Newton± Wigner density of mass position are remarkably dierent in strongly inhomogeneous ®elds and result i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 19 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…In the following three subchapters, treatment of PCE in electron density, Laplacian of electron density, and the Fourier transform of electron density (structure factors) is briefly presented. In general, it has been found that PCE dominantly affects the core electron density and properties related to electron density in the vicinity and/or at the nucleus, such as hyperfine coupling, , quadrupole moments, contact densities ,, and effective densities. , Properties related to electron density in the valence region (e.g., dipole moments and/or polarizabilities) are not affected by PCE and the same is found for the electron density itself. ,,, Nevertheless, a common exploration of PCE in electron density, its Laplacian or Fourier transform for compounds of heavy elements is being worthwhile. Foremostly, the direct comparison to the relativistic as well as electron correlation effects is to be addressed, including the radial significance with respect to the core region and the relevance on differences in structure factors with respect to sin­(θ)/λ.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the following three subchapters, treatment of PCE in electron density, Laplacian of electron density, and the Fourier transform of electron density (structure factors) is briefly presented. In general, it has been found that PCE dominantly affects the core electron density and properties related to electron density in the vicinity and/or at the nucleus, such as hyperfine coupling, , quadrupole moments, contact densities ,, and effective densities. , Properties related to electron density in the valence region (e.g., dipole moments and/or polarizabilities) are not affected by PCE and the same is found for the electron density itself. ,,, Nevertheless, a common exploration of PCE in electron density, its Laplacian or Fourier transform for compounds of heavy elements is being worthwhile. Foremostly, the direct comparison to the relativistic as well as electron correlation effects is to be addressed, including the radial significance with respect to the core region and the relevance on differences in structure factors with respect to sin­(θ)/λ.…”
Section: Methodsmentioning
confidence: 99%
“…According to eq , diagonalization of the Dirac–Coulomb Hamiltonian simultaneously accounts for a change of the resulting quasirelativistic wave function Ψ̃. ,, This was recognized in the physics realm already with the introduction of the free particle Foldy–Wouthuysen transformation, and has been later explored also in the quantum chemistry community. , Why picture change affects a particular property at the quasirelativistic level of theory can be understood by the inspection of the formal mapping between the expectation value of a general property operator X̂ in the Dirac picture (Ψ) and the unitary transformed IOTC picture (Ψ̃): ,,, …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Atomic Mean Field spin-orbit operator (AMFI) [71,72,73] and/or the 2e spin-orbit interaction have not been accounted for in the calculations. The treatment of Picture Change Error (PCE) [74,68,75,76,77,78,79] has not been considered within this study. Nevertheless, it has been shown that PCE in the 1c spin density of the [OsCl 5 (Hpz)]…”
Section: Computational Detailsmentioning
confidence: 99%
“…Therefore, it can lead to large differences in calculations of properties in a two-component framework. It is noted that the difference between ρ + and ρ 2c is significant mainly deep in the atomic cores and to some extent in the outer atomic core shells of heavy atoms [5,75,76]. In the valence regions of light and heavy atoms, the four-component and the two-component densities are very similar.…”
Section: Picture Changementioning
confidence: 95%